Meeting Patients Where They Are: Evaluating a Student-Run, Shelter-Based Model for Connecting Homeless Patients with a Medical Home - Aaron Matthew Brug; Georgiana Green; Scott I. Mayer; Maren Gregersen; Joseph Kanter; Catherine E. Jones (Journal of Student-Run Clinics, 2020)
Background: Substantial barriers exist between persons experiencing homelessness and the health care system, which contributes to significant health disparities. Innovations to connect patients to long-term primary care via the ‘medical home’ model have had mixed results. This study evaluates the effectiveness of an innovative, student-run, shelter-based clinic model that leverages its onsite location to link patients to a medical home.Methods: A retrospective chart review of patient visits at two shelter-based, student-run clinics between October 1, 2016 and October 1, 2017 was performed. Data collected included demographics, health risk factors, medical histories, and visit chief concerns. Patients referred to a medical home were assessed for successful follow-up at that location within 90 days. Successful medical home follow-up attendance was modeled using multivariable logistic regression with backwards elimination and a significance threshold of p<0.05.Results: Within 90 days of referral, 30% of all patients referred to the medical home successfully attended a follow-up appointment, with 57% of new patients attending more than one appointment in the same time interval. Among patients who received referrals, those with a mental health related chief complaint were significantly more likely to follow-up at a medical home than those with other chief complaints (p=0.024). Medicaid insurance status negatively predicted successful follow-up (p=0.041).Conclusions: Student-run free clinics in locations that access vulnerable populations can be effectively used to link patients to medical homes. A better understanding of these factors may provide insight into how to help patients access a medical home and establish longitudinal care.